2010
DOI: 10.1159/000292502
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular Risk Factors and Triggers in Transient Global Amnesia Patients with and without Jugular Valve Incompetence: Results from a Sample of 243 Patients

Abstract: Background/Aims: Different etiologies for transient global amnesia (TGA) have been proposed, such as venous flow abnormalities, spreading depression and migraine-related mechanisms like focal ischemia. Jugular vein valve incompetence (JVI) is commonly described in TGA patients, but its contributing role in TGA pathogenesis is still unknown. We investigated the possible relationship between JVI and pathogenetic mechanisms in TGA. Methods: 243 TGA patients underwent clinical and neurological assessment. Demograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 31 publications
1
33
0
Order By: Relevance
“…An animal study indicated that acute emotional and behavioral stress impaired long-term potentiation and increased long-term depression in CA1 neurons, and also disrupted hippocampus-dependent memory [23]. Recent research has suggested that one of the main pathogenic mechanisms of TGA is jugular valve incompetence, leading to venous congestion, ischemia, and vasogenic edema, but this proposal remains controversial [14,24]. At present, several hypotheses remain possible and no unequivocal evidence indicates that hippocampal lesions cause TGA.…”
Section: Discussionmentioning
confidence: 99%
“…An animal study indicated that acute emotional and behavioral stress impaired long-term potentiation and increased long-term depression in CA1 neurons, and also disrupted hippocampus-dependent memory [23]. Recent research has suggested that one of the main pathogenic mechanisms of TGA is jugular valve incompetence, leading to venous congestion, ischemia, and vasogenic edema, but this proposal remains controversial [14,24]. At present, several hypotheses remain possible and no unequivocal evidence indicates that hippocampal lesions cause TGA.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, cerebral ischemia in terms of thromboembolic etiology or hemodynamics was investigated through several case-control studies in comparison with transient ischemic attack (TIA), but did not find an association between TGA and cardiovascular risk factors [6,7,8,9,10,11]. Those studies focused on arterial ischemia considering an abrupt onset of TGA or an MRI finding, but recent studies are in search of venous congestion with subsequent ischemia combined with jugular valve insufficiency [4,12,13,14,15,16]. However, the question still remains whether cardiovascular risk factors are related to the occurrence of TGA at all.…”
Section: Introductionmentioning
confidence: 99%
“…Recent literature has suggested that restriction of extracranial venous drainage may be a risk factor in the development of MS. [1][2][3] Published series of treatment with angioplasty and/or stent placement have begun to emerge based on this yet unproved hypothesis. 4,5 Jugular venous pathology has also been linked with transient global amnesia 6,7 and migraines, [8][9][10][11] though this is controversial 11 and no clear etiologic link to venous pathology has been established for either disease.…”
mentioning
confidence: 99%